An occlusion paradigm to assess the importance of the timing of the quiet eye fixation - Vine, S. J.; Lee, D. H.; Walters-Symons, R.; Wilson, M. R. (European Journal of Sport Science, 2016)
The aim of the study was to explore the significance of the `timing` of the quiet eye (QE), and the relative importance of late (online control) or early (pre-programming) visual information for accuracy. Twenty-seven skilled golfers completed a putting task using an occlusion paradigm with three conditions: early (prior to backswing), late (during putter stroke), and no (control) occlusion of vision. Performance, QE, and kinematic variables relating to the swing were measured. Results revealed that providing only early visual information (occluding late visual information) had a significant detrimental effect on performance and kinematic measures, compared to the control condition (no occlusion), despite QE durations being maintained. Conversely, providing only late visual information (occluding early visual information) was not significantly detrimental to performance or kinematics, with results similar to those in the control condition. These findings imply that the visual information extracted during movement execution - the late proportion of the QE - is critical when golf putting. The results challenge the predominant view that the QE serves only a pre-programming function. We propose that the different proportions of the QE (before and during movement) may serve different functions in supporting accuracy in golf putting.